Factors of learners’ foreign language anxiety on second language acquisition - Kathrin Meylida Annur; Nasrullah Nasrullah (Universitas PGRI Madiun, 2023)
In second language acquisition, foreign language anxiety (FLA) is still happening up to the present time. Many studies show that FLA mostly interferes with learners' language learning and always appears among language learners with various factors. However, despite numerous studies on the topic, the factor of the occurrence of FLA in the context of second language acquisition is still rarely discussed. Thus, this study aims to explore deeper the factors which affect learners' FLA in second language acquisition. This research employs a systematic literature review as the method of research. The data are gathered from several journals and articles from previous years related to learners’ FLA factors. The findings of this research give insight to educators in comprehending learners’ anxiety in second language acquisition with its factors. The implication of the study is to increase educators’ awareness of learners’ FLA so it will not affect learners’ performance in classroom language learning.